2020
DOI: 10.1128/aem.02105-20
|View full text |Cite
|
Sign up to set email alerts
|

Use of Flavin-Containing Monooxygenases for Conversion of Trimethylamine in Salmon Protein Hydrolysates

Abstract: Enzymatic processing of fish by-products for recovery of peptides (hydrolysates) is a promising technology to reach food grade ingredients of high nutritional quality. Despite this, their bitter taste and “fish” odor block implementation in food products and limit their economic potential. Trimethylamine (TMA) is a known contributor to malodor in fish. Current strategies to mask or remove the odor are either not effective or give rise to undesirable side effects. As an alternative approach to remediate TMA, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…To investigate whether the mFMO variants had increased thermal stability compared to the native enzyme, we conducted protein melting studies using circular dichroism. The melting temperature ( T m ) of native mFMO was measured to be 46.2 °C (Table 3), which is in line with previous results (Goris et al, 2020). All mFMO variants demonstrated increased temperature stability compared to the wildtype enzyme, as reflected by their T m values, which ranged from 50.9 °C for mFMO_28 to 55.2 °C for mFMO_20 (Table 3).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…To investigate whether the mFMO variants had increased thermal stability compared to the native enzyme, we conducted protein melting studies using circular dichroism. The melting temperature ( T m ) of native mFMO was measured to be 46.2 °C (Table 3), which is in line with previous results (Goris et al, 2020). All mFMO variants demonstrated increased temperature stability compared to the wildtype enzyme, as reflected by their T m values, which ranged from 50.9 °C for mFMO_28 to 55.2 °C for mFMO_20 (Table 3).…”
Section: Resultssupporting
confidence: 91%
“…All 7 mFMO mutant variants were expressed with a C-terminal hexa-histidine tag, at levels comparable to that of native mFMO, purified (Figure S2), and verified by mass spectrometry. When expressing mFMO in Escherichia coli , the culture medium turns blue due to the enzymatic conversion of endogenous indole to indigo (Choi et al, 2003; Fabara and Fraaije, 2020; Goris et al, 2020). The fact that the culture media of all mFMO variants turned blue following overnight expression suggested that the expressed mFMO variants were functional.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a precursor of trimethylamine (TMA), trimethylamine oxide (TMAO) widely exists in aquatic products [ 52 ]. In the process of frying tilapia, the oxide is decomposed and produces the main odor substance trimethylamine under the action of enzymes [ 53 ], forming the characteristic flavor and slightly fishy odor of fried tilapia.…”
Section: Resultsmentioning
confidence: 99%
“…For determination, [total protein]: 5 μg ml −1 ; [substrates]: 25 mM; [pyridoxal phosphate]: 1 mM; reaction volume: 200 μL; T: 4-85 °C; and pH: 8.0 (50 mM Tris-HCl buffer). Aldo-keto reductase activity was determined using acetophenone as a substrate and NADPH as a cofactor, by following the consumption of NADPH at 340 nm (extinction coefficient, 6220 M −1 cm −1 ), as described 76 . For determination, [total protein]: 5 μg ml −1 ; [substrate]: 1 mM; [cofactor]: 1 mM; reaction volume: 200 μL; T: 4–85 °C; and pH: 8.0 (50 mM Tris-HCl buffer).…”
Section: Methodsmentioning
confidence: 99%